Eficacia tras la osteosíntesis en cara antero inferior y superior de fracturas de clavícula - Pretell Vargas, Johann Luis (2017)
OBJECTIVE: Determine if there is a difference in functional recovery and cosmetic outcome between surgical treatment after the anteroinferior and superior approach in adult patients with humeral shaft fracture treated at the Hospital Victor Lazarte Echegaray, during the period from 01/09/11 to 30/06/16. METHOD AND MATERIALS: It´s a study of two comparative, retrospective and analytical groups, consisting of patients diagnosed with clavicle fracture osteosynthesis indicating plate and screws, divided into two groups of 26 patients each selected according technique approach. Functional recovery was measured by Quick DASH Score and cosmetic result with the Visual Analogue Scale. RESULTS: We found that postoperative functional recovery, according to the Quick DASH score of 6 months to more, had a score of 6.56 ± 2,82 and 10,40 ± 4,12 in patients with anteroinferior and superior approach, respectively (p = 0,0003). The frequency of late morbidity was 46,15% and 92,31% anteroinferior and superior approach, respectively (p = 0,0003). In cosmetic results, patients were very satisfied in 38,46%, satisfied in 57,59% and dissatisfied in 3,85% in patients with anteroinferior approach; while patients with superior approach, very satisfied in 3.9%, 88,46% satisfied and dissatisfied in 7,69% (p = 0,0092). CONCLUSION: Anteroinferior osteosynthesis is more effective than superior in clavicle diaphyseal fractures.